Madness and literature : Foucault’s encounter - Kelmendi, Labinot (Array, 2020)
The purpose of this paper is to outline the connection between literature, madness and language in Foucault’s philosophy. In the first part of the paper, these three discursive bases are situated in the “cosmos of madness” in the sense of what Serres calls “the archaeology of psychology” and Caputo “the deconstruction of psychology”. This part marks the language of literature as a decomposing space of the “tribunal of the cogito” (Derrida). The second part explicates the impetus of “literature language”, trying to promote lunatic manifestations that are the works of three authors, Dostoevsky, De Sade and Artaud, and how their work has a symbiotic connection with the work of Foucault. The paper ends with the connection of the unreasonable and parrēsia as an opportunity that could be manifested only in literature as a habitus to exist in. Finally, as Foucault notes, the “language of literature” is the “language of madness” or the possibility of freedom of the expression of our Being.